GLOBAL TRANSFORMATION OF THE ROLE OF ACCOUNTING AND CONTROL IN THE DIGITAL ECONOMY - MURAVSKYI, Volodymyr; SHEVCHUK, Oleg (Scientific journal «World of Finance», 2024)
Introduction. An actual stage of the development of the global socio-economic system is the formation of the digital economy. The information basis of the digital economy is accounting and control, which undergo positive changes under the conditions of the use of innovative computer and communication technologies. The transformation of accounting and control takes place through the clarification of their global roles, manifested in the digital economy.The purpose of the article is to highlight and clarify the global role of accounting and control under the influence of the use of computer and communication technologies in the conditions of the formation of the digital economy.Results. In order to assess the readiness of the socio-economic system to implement the principles of the digital economy, an assessment of the country’s innovativeness, the level of implementation of information processing technologies and the digital capacity of the economy was carried out. The results of the ranking of countries by the level of development of the digital economy proved the presence of active obstacles to the digitalization of socio-economic processes, overcoming which involves the optimization of accounting and control systems. Regardless of the national or international features of business, seven global roles of accounting and control in the digital economy are identified: informativeness, integration, communication, institutionality, control, optimization, and protection. accounting and control in the conditions of the formation of the digital economy. It has been proven that a common feature for all global roles of accounting and control in the digital economy is the priority of electronic transactions in the financial and economic activities of enterprises compared to classic monetary and commodity transactions.Conclusions. Only in a socio-economic system with a predominant part of electronic transactions among monetary and commercial operations is it possible to comprehensively activate the above global roles of accounting and control. Highlighting the global roles of accounting and control forms the starting point in the study of the vectors of further digitization of accounting information processing in relation to the digital economy. For the development of a comprehensive understanding of the prospects for the transformation of accounting and control, further scientific research into the substantiation of the impact of computer and communication technologies, which are the basis of the digital economy, on the order of processing accounting information is important.